The marmoset monkey as a model for visual neuroscience. (April 2015) - Mitchell, Jude F.; Leopold, David A.
Highlights: The marmoset offers an excellent complement to the macaque as a model for visual neuroscience. The marmoset brain bears most of the organizational features of other primates. Marmoset natural gaze behavior closely resembles that of other primates, and marmosets can be trained to perform visual tasks. Marmosets provide advantages for modern neurophysiology techniques including optical imaging. Abstract: The common marmoset ( Callithrix jacchus ) has been valuable as a primate model in biomedical research. Interest in this species has grown recently, in part due to the successful demonstration of transgenic marmosets. Here we examine the prospects of the marmoset model for visual neuroscience research, adopting a comparative framework to place the marmoset within a broader evolutionary context. The marmoset's small brain bears most of the organizational features of other primates, and its smooth surface offers practical advantages over the macaque for areal mapping, laminar electrode penetration, and two-photon and optical imaging. Behaviorally, marmosets are more limited at performing regimented psychophysical tasks, but do readily accept the head restraint that is necessary for accurate eye tracking and neurophysiology, and can perform simple discriminations. Their natural gaze behavior closely resembles that of other primates, with a tendency to focus on objects of social interest including faces. Their immaturity at birth and routine twinning also makes them ideal for the study of postnatal visual development. These experimental factors, together with the theoretical advantages inherent in comparing anatomy, physiology, and behavior across related species, make the marmoset an excellent model for visual neuroscience.